Fabrication of thin targets of 160Gd by thermal evaporation technique. (November 2017) - Kavita,; Abhilash, S.R.; Kabiraj, D.; Golda, K.S.; Chopra, Sundeep; Ojha, Sunil; Umapathy, G.R.; Mehta, D.; Singh, Gurjot; Kumar, Sanjeev; Kumar, Rakesh; Singh, Hardev
Abstract: Thin 160 Gd targets (enrichment 98.12%) in the thickness range of 45–55 μg/cm 2 have been prepared on carbon backing in the high vacuum environment using thermal evaporation technique. During the fabrication, a few of the challenges faced were the oxidizing tendency of Gd in the atmosphere, limited amount of enriched material and the peeling off problem during floating of the films. Several trials were first conducted with natural Gd to optimize different parameters of the fabrication process. By utilizing only 30 mg of enriched isotopic material, more than 25 targets of 160 Gd were fabricated successfully. The purity check and thickness measurement of the prepared targets were performed using Energy Dispersive X-Ray Fluorescence and Rutherford Back Scattering techniques. Absence of any heavy ions and presence of negligible amount of oxygen in the prepared films revealed the purity of the targets fabricated using thermal evaporation technique. Highlights: Thin (∼50 μg/cm 2 ) targets of isotopically enriched 160 Gd on carbon backing has been prepared for the the first time. A flash of carbon topping was done in order to avoid the oxidation of the targets. Thin targets are required for the fission fragment mass distribution measurements in medium mass region. Thin targets are important for such studies so as to minimize the energy loss of heavy reaction products inside the target materials.